1995
DOI: 10.1074/jbc.270.29.17616
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Activation of Ca2+-Calmodulin-dependent Protein Kinase IV by Ca2+-Calmodulin-dependent Protein Kinase Ia Kinase

Abstract: Purified pig brain Ca(2+)-calmodulin (CaM)-dependent protein kinase Ia kinase (Lee, J. C., and Edelman, A. M. (1994) J. Biol. Chem. 269, 2158-2164) enhances, by up to 24-fold, the activity of recombinant CaM kinase IV in a reaction also requiring Ca(2+)-CaM and MgATP. The addition of brain extract, although capable of activating CaM kinase IV by itself, provides no further activation beyond that induced by purified CaM kinase Ia kinase, consistent with the lack of a requirement of additional components for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 61 publications
5
117
0
Order By: Relevance
“…These characteristic features of the recombinant CaM-KIV used in this study, including generation of autonomous activity by activation and kinetic parameters of the enzyme (K m for ATP ϭ 27 M and K m for syntide-2 ϭ 264 M, Fig. 5C), were similar to the previous results obtained using enzymes expressed in Sf9 cells (16,17,19). We also performed similar experiments using CaM-KI and the same concentration (3 g/ml) of CaM-KK as used for CaM-KIV activation (Fig.…”
Section: Activation and Phosphorylation Of Cam-kiv And Cam-ki Bysupporting
confidence: 79%
See 2 more Smart Citations
“…These characteristic features of the recombinant CaM-KIV used in this study, including generation of autonomous activity by activation and kinetic parameters of the enzyme (K m for ATP ϭ 27 M and K m for syntide-2 ϭ 264 M, Fig. 5C), were similar to the previous results obtained using enzymes expressed in Sf9 cells (16,17,19). We also performed similar experiments using CaM-KI and the same concentration (3 g/ml) of CaM-KK as used for CaM-KIV activation (Fig.…”
Section: Activation and Phosphorylation Of Cam-kiv And Cam-ki Bysupporting
confidence: 79%
“…CaM-KK-It has been shown that CaM-KIV is phosphorylated at Thr 196 by CaM-KK, resulting in induction of a high level of Ca 2ϩ /CaM-dependent activity as well as generation of Ca 2ϩ / CaM-independent activity (17)(18)(19). Because CaM-KIV undergoes autophosphorylation of multiple residues subsequent to activation (36 -38), the relationship between activation of the kinase activity and Thr 196 phosphorylation has not been precisely determined in vitro.…”
Section: Activation and Phosphorylation Of Cam-kiv And Cam-ki Bymentioning
confidence: 99%
See 1 more Smart Citation
“…We treated SH-SY5Y cells for various times with thapsigargin and monitored CaM-stimulated protein kinase activity in the cell homogenate using the CaM kinase-selective substrate syntide-2. This peptide has been used to measure CaMK IV activity in vitro (43,62,63). Syntide-2 is homologous to phosphorylation site 2 of glycogen synthase (64).…”
Section: Ca 2ϩ /Cam-stimulated Protein Kinase Activity Reduction Is Amentioning
confidence: 99%
“…As is the case for other CaM kinases, the active site of CaMKIV is sterically blocked by an autoinhibitory domain that prevents substrate binding to the enzyme. Binding of Ca 2ϩ /CaM to this region relieves autoinhibition by repositioning the autoinhibitory domain and exposes a critical residue in the activation loop, T200, to CaMKK-mediated phosphorylation (19,20). T200 phosphorylation increases CaMKIV activity and leads to the generation of Ca 2ϩ /CaM-independent, or autonomous, activity.…”
mentioning
confidence: 99%